Visual Character Analysis of Akutagawa Ryuunosuke In Bungou to Alchemist Using Manga Matrix Theory - Hermawan, Aisha Namina Farani Putri; Rahman, Yanuar; Putra, I Dewa Alit Dwija (Bina Nusantara University, 2026)
In recent years, games have become one of the most prominent forms of entertainment, appealing to players from diverse backgrounds and age groups. As the gaming industry continues to expand, the variety of genres and artistic styles grows as well, offering players increasingly rich and multifaceted experiences. One major factor shaping these experiences is visual design, particularly the creation and presentation of characters. Character design goes beyond mere aesthetics, it functions as a visual language that conveys narrative depth, emotional nuance, and meaning. In Bungou to Alchemist, character visuals play a central role in expressing each character’s personality and literary origins. Designers meticulously craft every aspect of the characters from their clothing and accessories to reflect their backgrounds and narrative roles. Akutagawa Ryuunosuke exemplifies this thoughtful approach. His design incorporates elements closely tied to the themes of his writing, such as sharp facial features, muted color palettes, and an overall atmosphere of intensity and restraint. This study utilizes the Manga Matrix method to analyze these visual elements, aiming to uncover the deeper significance embedded in each artistic choice. Through this analysis, the research demonstrates how deliberate design decisions shape player perception, deepen emotional involvement, and ultimately contribute to a more immersive and engaging gameplay experience.